Karakteristik dan Distribusi Sampah Laut Makro di Pesisir Teluk Ambon - Fahrul Rozy Fakaubun; Muhammad Fahrul Barcinta; Milyan Uli Latue; Eva S. Ratuluhain; Imanuel V. T. Soukotta; Valentine D. Saleky (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2026)
Marine debris has become a major environmental concern in coastal areas, particularly in semi-enclosed waters such as Ambon Bay. This study aimed to analyze the characteristics of macro marine debris based on material composition, quantity, mass, and density across four coastal monitoring stations in Ambon Bay. Field surveys were conducted in December 2025 using the shoreline transect method in accordance with the national marine debris monitoring guidelines. Macro debris larger than 2.5 cm was collected, classified by material type, counted, and weighed. Variations in material composition were assessed using the Shannon–Wiener diversity index (H'), while differences in debris mass among stations were analyzed using the non-parametric Kruskal–Wallis test. The results showed that plastic was the dominant material at all stations, resulting in low material diversity. Significant spatial differences in macro marine debris mass were also observed among the stations, with Poka exhibiting the highest debris accumulation, whereas Lateri showed a relatively more diverse material composition than the other stations. These findings indicate that the characteristics of macro marine debris vary spatially across Ambon Bay, highlighting the need for site-specific management strategies to support more effective coastal marine debris control